2019
DOI: 10.1016/j.ygyno.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced memory-like natural killer cells have enhanced function, proliferation, and in vivo expansion against ovarian cancer cells

Abstract: Objective: Natural killer (NK) cells are lymphocytes well suited for adoptive immunotherapy. Attempts with adoptive NK cell immunotherapy against ovarian cancer have proven unsuccessful, with the main limitations including failure to expand and diminished effector function. We investigated if incubation of NK cells with interleukin (IL)-12, IL-15, and IL-18 for 16 hours could produce cytokine-induced memory-like (CIML) NK cells capable of enhanced function against ovarian cancer. Methods: NK cells were preacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 39 publications
4
64
0
Order By: Relevance
“…Cytokine-induced memory-like (CIML) NK cells refers to NK cells,when pre-activated with IL-12, IL-15, and IL-18, may exhibit enhanced function when re-activated following a resting period cultured with low dose IL-15 9 . CIML NK cells have enhanced anti-leukemic and anti-tumor capacity over conventional NK cells 10,11 . However, the role of CIML NK cells in autoimmunity remains to be determined.…”
mentioning
confidence: 99%
“…Cytokine-induced memory-like (CIML) NK cells refers to NK cells,when pre-activated with IL-12, IL-15, and IL-18, may exhibit enhanced function when re-activated following a resting period cultured with low dose IL-15 9 . CIML NK cells have enhanced anti-leukemic and anti-tumor capacity over conventional NK cells 10,11 . However, the role of CIML NK cells in autoimmunity remains to be determined.…”
mentioning
confidence: 99%
“…IL-12/15/18-preactivated NK cells have emerged as a powerful tool to treat leukemia 11 , and their potential is also being explored in therapies against other malignancies [13][14][15]17 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed similar behavior of human IL-12/15/18stimulated NK cells, showing an enhanced cytokine production following restimulation 11,13,[20][21][22][23][24] , and increased proliferation 11,13,20 . After IL-12/15/18-stimulation, the phenotype of NK cells includes changes in the expression of activating and inhibitory receptors, and chemokine and cytokine receptors 11,13,20,22,[25][26][27] . Interestingly, it has been also demonstrated that cytokine-stimulation modifies the metabolic activity of NK cells 28,29 , although this aspect has been poorly explored in human IL-12/15/18-stimulated NK cells.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations